IMPROVING THE PERFORMANCE OF A CHOIR LEADER - Vasilchenko Olga Anatolevna (Galaxy International Interdisciplinary Research Journal, 2024)
This article examines the development of professional choral art and the activities of the choir director in Uzbekistan, as well as the conditions for its development. The improvement of the activities of the director of the choir and those working in this creative field is also touched upon.